The off-target effects of AID in carcinogenesis - Junna Jiao; Zhuangwei Lv; Yurong Wang; Liye Fan; Angang Yang; Angang Yang; Angang Yang (Frontiers in Immunology, 2023)
Activation-induced cytidine deaminase (AID) plays a crucial role in promoting B cell diversification through somatic hypermutation (SHM) and class switch recombination (CSR). While AID is primarily associated with the physiological function of humoral immune response, it has also been linked to the initiation and progression of lymphomas. Abnormalities in AID have been shown to disrupt gene networks and signaling pathways in both B-cell and T-cell lineage lymphoblastic leukemia, although the full extent of its role in carcinogenesis remains unclear. This review proposes an alternative role for AID and explores its off-target effects in regulating tumorigenesis. In this review, we first provide an overview of the physiological function of AID and its regulation. AID plays a crucial role in promoting B cell diversification through SHM and CSR. We then discuss the off-target effects of AID, which includes inducing mutations of non-Igs, epigenetic modification, and the alternative role as a cofactor. We also explore the networks that keep AID in line. Furthermore, we summarize the off-target effects of AID in autoimmune diseases and hematological neoplasms. Finally, we assess the off-target effects of AID in solid tumors. The primary focus of this review is to understand how and when AID targets specific gene loci and how this affects carcinogenesis. Overall, this review aims to provide a comprehensive understanding of the physiological and off-target effects of AID, which will contribute to the development of novel therapeutic strategies for autoimmune diseases, hematological neoplasms, and solid tumors.